Efficient utilization of rateless LDPC codes for satellite broadcasting services - Meixiang Zhang; Chunxiao Li; Sooyoung Kim (International Conference on Wireless Communications and Signal Processing, 2016)
This paper proposes an efficient rateless low-density parity check (LDPC) codes for satellite broadcasting system. The proposed scheme uses the conventional LDPC codes specified in recent digital video broadcasting via satellite (DVB-S) standards, and concatenate them with Luby transform (LT)-like codes in order to form systematic rateless codes. In this way, redundant parities can be made at the transmitter and re-transmitted whenever decoding of the conventional LDPC codes is failed. We also present a compact joint iterative decoding algorithm for the proposed rateless LDPC codes. As an application example of the proposed codes, hybrid automatic repeat request (HARQ) scheme for the satellite system is introduced. The simulation results investigated in this paper reveal that the proposed rateless LDPC code can provide performance enhancement over the conventional LDPC codes. We can expect that the proposed code can be effectively utilized in the satellite system.